Pyridine mediated supramolecular assemblies of 3,5-dinitro substituted benzoic acid, benzamide and benzonitrile - Arora, KK; PrakashaReddy, J; Pedireddi, VR (Tetrahedron, 2005)
Synthesis and characterization of molecular assemblies of pyridine adducts, la, 2a and 3a, of 3,5-dinitrobenzoic acid, 1, 3,5-dinitrobenzamide, 2 and 3,5-dinitrobenzonitrile, 3, respectively, have been reported. All these adducts were obtained by crystallization of 1, 2 and 3 from pyridine. However, crystallization of I from pyridine in the presence of benzene resulted in the formation of a pyridinium adduct, 1b, along with a water molecule. All the adducts crystallize in a 1: 1 molecular ratio except la, which forms a 1:2 adduct, as characterized by single crystal X-ray diffraction method. The adducts crystallize in different space groups-la, orthorhombic, Pna2(1); 1b, monoclinic, P2(1); 2a, monoclinc, C2/c; 3a, triclinic, P-1. In two-dimensional arrangement, la, 1b and 3a form sheet structures. In la, within the two-dimensional sheets, large cavities are formed, which are occupied by pyridine molecules. In 1b, the sheets are catenated to form a chicken-wire network. However, 2a formed a crossed ribbon packing pattern with empty channels in the three-dimensional structure. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: 3; 5-dinitrobenzamide; 5-dinitrobenzoic acid; 5-dinitrobenzonitrile; channel structures; host-guest complexes; layered structures; molecular recognition; Pyridine